Foreign Affairs Litigation in United States Courts. - Moore, John Norton (Sokol Colloquium., 2013)
Foreign Affairs Litigation in United States Courts is an indispensable resource for attorneys and government officials focused on the role of the courts in foreign affairs, actions against foreign governments in United States courts, the Act of State Doctrine, foreign sovereign immunity, the Foreign Claims Settlement Commission, foreign affairs takings actions in the Court of Federal Claims, and choice of court in international litigation.